The abundance of fruit bats in UiTM Kuala Pilah and its morphometric analysis / Muhammad Fakhrudin Mohd Nokin and Nur Hasyimah Ramli - Mohd Nokin, Muhammad Fakhrudin; Ramli, Nur Hasyimah (UiTM Cawangan Negeri Sembilan, 2022)
There are currently few records of anthropogenic effects on bat composition, particularly in Malaysia. The objectives of this study are to determine the abundance and growth rate of bats at UiTM Negeri Sembilan Kampus Kuala Pilah (UiTMCNS). Mist nets with 2.5 x 9 x 4cm in size were set up at five checkpoints for sample collection, followed by species identification and morphological measurement of each sample. A total of 13 individuals of Cynopterus brachyotis and 9 individuals of Macroglossus minimus were collected from 4 checkpoints (checkpoint 1, 2, 3 and 5), with non-individual of bat was collected from checkpoint 4. The number of C. brachyotis and M. minimus were recorded at checkpoint; 1 (6, 4) individual, 2 (3, 2) individuals, 3 (3, 1) individuals and 5 (1, 2) individuals, respectively. Both C. brachyotis and M. minimus are classified as fruit bats. The Length-Weight Regressions (LWRs) of both species caught shows positive allometric growth as the 'b' value is more than 3. The parabolic form of LWRs for this study is W=24.384L4.853. The result of LWRs analysis prove that the study area is still suitable to become the fruit bat's habitat. This research will help to increase data on bats composition in Negeri Sembilan, especially UiTMCNS. The data also can be used as a guideline for future researchers and important for conservation planning of the species in Negeri Sembilan.